Implementation of the BOOST Elementary Program (Optimal Learning with Educated Students) to Improve Reading Literacy Skills of Botok Magetan State Elementary School Students - Aprillia Sinda Dinningrum; Laili Arin Ramadhani; Fadhillah, Nisa’ul (Journal of Dedication in Community, 2024)
The BOOST SD (Optimal Learning with Educated Students) program is implemented at SD Negeri Botok, Magetan, to improve the reading literacy skills of students in grades 1 to 3 with low literacy levels. This program lasts three months, from September to November 2023, with stages of need identification, development of learning tools, implementation, and evaluation. The methods used include initial observation, discussion with teachers, and the development of tools such as textbooks, visual presentations, and assessment instruments. The evaluation was carried out through pre-test and post-test, showing a significant improvement in students' reading ability, especially in letter recognition, word reading, and sentence reading. The program emphasizes the importance of targeted interventions and can serve as a practical model for addressing literacy challenges in other primary schools.